PELESTARIAN TARIAN TRADISIONAL BUDAYA INDONESIA - Wa Ode Salsa; Amelia Agusman, Nur; Christanti Kaluti, Norverlita; Nurwidyayanti; Andi Agusniati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Traditional dance is a form of Indonesian cultural heritage embodying historical, philosophical, and cultural values that must be preserved amidst the changing times. The era of globalization characterized by advancements in information and communication technology has brought about significant shifts in the mindsets and lifestyles of the public, particularly the younger generation, thereby influencing interest in traditional arts. This article aims to analyze the preservation of traditional dance as Indonesian cultural heritage in the globalization era and to identify strategies for ensuring its continuity. The study employs a library research method with a qualitative descriptive approach. Data were gathered from various scholarly journals discussing globalization, traditional dance, the role of the younger generation, and the use of digital media in cultural preservation. Data analysis was conducted using content analysis techniques, involving the review, categorization, and interpretation of findings from previous studies. The results indicate that globalization has significantly contributed to a decline in the younger generation's interest in traditional dance due to the dominance of global popular culture. However, globalization also presents new opportunities through the use of digital media as a platform for promotion, education, and artistic innovation. Furthermore, the involvement of the younger generation through education, training, and cultural activities has proven crucial in strengthening the preservation of traditional dance. Thus, sustainable cultural preservation can be achieved through synergy among digital technology, educational institutions, the community, and the younger generation.